2012
DOI: 10.1115/1.4023093
|View full text |Cite
|
Sign up to set email alerts
|

Murray's Law in Elastin Haploinsufficient (Eln+/−) and Wild-Type (WT) Mice

Abstract: Using either the principle of minimum energy or constant shear stress, a relation can be derived that predicts the diameters of branching vessels at a bifurcation. This relation, known as Murray's Law, has been shown to predict vessel diameters in a variety of cardiovascular systems from adult humans to developing chicks. The goal of this study is to investigate Murray's Law in vessels from mice that are haploinsufficient for the elastin protein (Eln+/−). Elastin is one of the major proteins in the blood vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…Comparing these geometry-based estimates of pressure with the adjusted measured systolic pressures in Table 1 revealed that the values corresponded well, in general (percent error < 15%). This finding suggests a possible normal, or adaptive, growth and remodeling in response to changes in either genotype or pharmacologic treatment for most of the cases studied, which is consistent with the report by Sather et al 44 that arterial caliber was well adapted in an elastin haploinsufficient mouse model ( Eln +/− ). A similar analysis of the Aortic Banding model revealed values of ε ranging from 0.83 (0 day) to 1.91 (10–14 day) and γ ranging from 0.94 (0 day) to 2.59 (35–56 day); the actual data suggest a value of ε ~ 2 at the 7–10 day period but only a maximum value of γ ~1.28 at 10–14 days 12 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Comparing these geometry-based estimates of pressure with the adjusted measured systolic pressures in Table 1 revealed that the values corresponded well, in general (percent error < 15%). This finding suggests a possible normal, or adaptive, growth and remodeling in response to changes in either genotype or pharmacologic treatment for most of the cases studied, which is consistent with the report by Sather et al 44 that arterial caliber was well adapted in an elastin haploinsufficient mouse model ( Eln +/− ). A similar analysis of the Aortic Banding model revealed values of ε ranging from 0.83 (0 day) to 1.91 (10–14 day) and γ ranging from 0.94 (0 day) to 2.59 (35–56 day); the actual data suggest a value of ε ~ 2 at the 7–10 day period but only a maximum value of γ ~1.28 at 10–14 days 12 .…”
Section: Discussionsupporting
confidence: 91%
“…Note, therefore, that the Acta2 −/− carotids were the only ones that were hypotensive (~81 mmHg) and the 35–56 day banding carotids were the only ones to have experienced an abrupt increase (from 120 to 154 mmHg at 7–14 days), then decrease (to 124 mmHg) in systolic blood pressure. In other words, it appears that “reverse” growth and remodeling (e.g., thinning of the wall) in response to decreases in pressure was much less adaptive than “positive” growth and remodeling in response to increases in blood pressure see, for example, previous results for Eln +/− carotids 44 as well as the Fbn1 mgR/mgR , Fbln5 −/− , Ang-II ApoE −/− , and Aortic Banding models at 7–10 and 10–14 days, all of which only experienced elevated pressures. That central arteries tend to adapt better, or quicker, to increases rather than decreases in pressure has been known since the important work of Wolinsky 53 and may have important implications regarding the clinical goal to reverse effects of established hypertension.…”
Section: Discussionmentioning
confidence: 93%
“…(1) and have also found that the data are in agreement with Murray's law [9,10]. Nevertheless, some of these studies [5,7,8,10] have reported that the scaling exponent, as determined by a least-squares fit to the data, differs slightly from 3 with the reported exponent being 2.7-3.0. How ever, considerable scatter exists in the data sets.…”
Section: Introductionmentioning
confidence: 75%
“…However, the Newto nian fluid assumption used in Murray's analysis is relaxed. Sev eral previous studies [8,[11][12][13] have suggested that discrepancies between experimental data and Murray's theory may be due to the rheological properties of blood. The goal of this work, therefore, is to test the hypothesis that deviations from the cubic scaling exponent may be in part due to blood's shear-thinning behavior.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation